1987
DOI: 10.1159/000156293
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of Adipose Tissue in Captive Macaca Monkeys and Its Implications for Human Biology

Abstract: In a sample of 31 sedentary, ad libitum-fed monkeys, most specimens had less than 5 % adipose tissue by weight. Total fatness correlated closely with the number of adipocytes per kilogram lean body mass, but not at all with mean adipocyte volume, except in specimens below 5 % fat. The total number of adipocytes per kilogram of lean body mass increased more than tenfold in the most obese specimens. These data suggest that, like humans but in contrast to laboratory rodents, adipocyte proliferation, not adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…It should be noted that although epididymal fat is considered as a visceral depot by many authors, it is not in fact found in humans. The human adipose organ in lean adults accounts for ϳ8 -18% of body weight in males and for 14 -28% in females (ϳ5% in monkeys) (84). The morphology of human adipose tissues is identical to that of murine tissues.…”
Section: The Human Adipose Organmentioning
confidence: 95%
“…It should be noted that although epididymal fat is considered as a visceral depot by many authors, it is not in fact found in humans. The human adipose organ in lean adults accounts for ϳ8 -18% of body weight in males and for 14 -28% in females (ϳ5% in monkeys) (84). The morphology of human adipose tissues is identical to that of murine tissues.…”
Section: The Human Adipose Organmentioning
confidence: 95%
“…The distribution of the visceral depots is very similar to that described in rodents, but the omental depot is particularly well developed in humans. In lean adults, the human adipose organ accounts for 8-18% of body weight in males and for 14-28% in females (w5% in monkeys) (88,89).…”
Section: The Human Adipose Organmentioning
confidence: 99%
“…They also showed that females tend to carry more fat than males. Pond and Mattacks (1987) reported a low fat percentage in captive-reared pigtailed (Macaca nemestrina) and long-tailed macaques (M. fascicularis). Tanaka et al (1995) regarded 35% as a criterion for obesity among captive-bred long-tailed macaques, based on division using the fat-free soft tissue mass as the denominator, its value being equivalent to about 25% using body mass as the denominator.…”
Section: Obesity and Leanness In Japanese Macaquesmentioning
confidence: 99%
“…Fat accumulation has been studied in various primates, including humans and other anthropoids (McFarland 1997), human infants (Kuzawa 1998;Pawlowski 1998), captive macaques (Pond and Mattacks 1987;Tanaka et al 1995), captive African hominoids (McFarland and Zihlman 1997), and wild orangutans (Knott 1997). Cheirogaleid lemurs, such as Cheirogaleus medius (Fietz and Ganzhorn 1999) and Microcebus murinus (Schmid 1999) are exceptional primates because they hibernate, relying on fat deposited in the tail.…”
mentioning
confidence: 99%